Restrictions on experiencer placement in German tough-movement: Constituency and prosody rather than intervention - Salzmann, Martin (Nordlyd, 2026)
In this paper, we will compare the syntax of English tough-movement with that of its translational equivalent in German. We will see that, on the one hand, the syntax of the German construction is very different: there is no A'-movement involved but rather A-movement and restructuring; additionally, the adjective is merged as an adjunct to the infinitival clause rather than being the head that selects it; on the other hand, we will see that one can observe similar restrictions on the placement of experiencers. We will argue that this suggests that many of the proposals that have been made to account for experiencer intervention in English cannot be applied to German. Instead, we will argue that the restrictions follow from independent properties of German such as (i) the constituency that obtains if German tough-movement essentially receives the same analysis as the modal passive and (ii) a general adjacency requirement on verb clusters.
Keywords: German; tough-movement; experiencer intervention; long A-movement; modal passive